2020
DOI: 10.1097/mjt.0000000000001076
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Therapy: Future Perspectives

Simona Cernea,
Itamar Raz

Abstract: Background: Insufficient insulin secretion is a core pathogenetic mechanism of diabetes mellitus and therefore, insulin therapy remains the cornerstone of management. Over the past 100 years, much progress has been made in the development of insulin therapy, including elaboration of novel insulin formulations and delivery methods. Areas of Uncertainty: Despite significant advances, there are still many barriers, challenges, and uncertainties involving i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 70 publications
0
30
0
2
Order By: Relevance
“…Treatment with initial insulin formulations showed both insulin-specific nAbs and antibodies to other drug components [44]. However, replacing impure animal insulins with highly purified porcine insulins and, more recently, recombinant and semisynthetic human insulin preparations has vastly reduced-although not completely eliminated-the occurrence of immunogenicity [44,51,52].…”
Section: Clinical Challenges Of Immunogenicity To Biologic Drugsmentioning
confidence: 99%
“…Treatment with initial insulin formulations showed both insulin-specific nAbs and antibodies to other drug components [44]. However, replacing impure animal insulins with highly purified porcine insulins and, more recently, recombinant and semisynthetic human insulin preparations has vastly reduced-although not completely eliminated-the occurrence of immunogenicity [44,51,52].…”
Section: Clinical Challenges Of Immunogenicity To Biologic Drugsmentioning
confidence: 99%
“…Finally, no differences were found in the efficacy or the risk of hypoglycemia when comparing Glar-300 and Deg-200 (Fig. 7) [58,[60][61][62]. On the other hand, studies have shown that, in relation to weight, Det showed less weight gain than NPH and Glar-100.…”
Section: Efficacy and Safety Of Bimentioning
confidence: 89%
“…On the other hand, studies have shown that, in relation to weight, Det showed less weight gain than NPH and Glar-100. Likewise, a lower weight gain was documented with Glar-300 than Glar-100 (Table 5) [38][39][40][56][57][58][59][60][61][62][63]. Moreover, when evaluating the average doses of BI, it was found that with the use of Deg-100, a lower dose was required (compared to Glar-100), while with Glar-300, a higher average dose was required (compared to Glar-100) [58,59].…”
Section: Efficacy and Safety Of Bimentioning
confidence: 99%
“…To obviate these restrictions, an immense variety of delivery methods were investigated to control blood glucose levels, including oral, nasal, pulmonary, and transdermal approaches, etc. [7][8][9]. Nevertheless, each of these methods encounters with some limitations including poor permeability across the barriers of body, possible allergic or irritation reactions, difficulty to achieve high plasma drug concentration, and low or variable bioavailability owning to degradation by proteolytic enzymes [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%